A narrativa transmídia no jornalismo factual de atualização contínua: a cobertura jornalística realizada pela BBC News Brasil no website, no Twitter e no Instragram - Santana, Adson Vinicius Santos (2019)
The present study starts from the following research problem: Do transmedia narratives in the digital environment change the textual structures and the experiences of the reader of daily factual journalism? From it, five working hypotheses were elaborated: Transmedia narrative enables greater contextualization of daily factual journalism by offering the reader greater narrative complexity and engagement in the news; Specific characteristics of digital journalism, applied in the coverage of daily journalism, are enhanced with transmedia narratives; The reader of daily journalism may experience a denser engagement with relevant everyday facts with transmedia narratives; Transmedia narrative enables the emergence of new genres and formats of daily journalism in the digital environment; The transmedia narrative increases the length of time the news is circulated to the public. The research was structured a methodology based on theoretical research and empirical research. The first step, therefore, consisted of bibliographic and documentary research, with analysis of recent literature on the aspects of temporality, traditional factual journalism and new media, journalistic genres in factual journalism and new media, media convergence, and transmedia narratives. Secondly, a case study was carried out, taking as its object an example of a multiplatform journalistic production: BBC News Brasil on its website, and on its Twitter and Instagram accounts. The collection took place over a period of three months (between April and May 2019) and consisted of the collection of headlines from the BBC NewsBrasilwebsite at two daily times. The data obtained were tabulated according to the following analysis categories, based on Jenkins (2009b) and Souza (2011): Drilling Capacity, Continuity X Multiplicity, Immersion x Extraction Capacity, Universe Construction, Subjectivity and Scattering. For data analysis, we used the Content Analysis method. The results indicated that the transmedia narrative on BBC News Brasil is still expetimental.